Patagonian ñire (Nothofagus antarctica) combined with green tea - Novel beverage enriched in bioactive phytochemicals as health promoters - Mattera, María Gabriela (2022)
Background: Polyphenol-enriched tea is an interesting product for food industries under the current consumer demands. This study aimed at evaluating the Nothofagus antarctica (NA) species as a valuable source of bioactive compounds as well as obtaining an optimized organic green tea (OGT)-NA blend. NA leaves of different developmental stages and several mixture proportions were analyzed. HPLC–DAD–ESI/MSn was used to identify and quantify the polyphenol compounds. Antioxidant capacity and the type of interaction occurring between constituents were assessed. Results: NA infusions exhibited high polyphenol diversity and some differences in the individual concentration were found between NA leaves. NA polyphenol profile showed great complementarity to the one present in green tea. Besides, NA impacted positively the antioxidant strength in the mixtures. Finally, the 67% OGT-33% NA blend exhibited an optimized performance in relative and total polyphenol contents and antioxidant properties, and thus, it could be recommended as a novel beverage. Conclusions: N. antarctica is a valuable source of polyphenol compounds and its combination with green tea, in a blend, could represent an interesting food product. In addition, this new non-wood product constitutes a novel productive strategy for adding value to the silvopastoral systems with positive socio-economic impact.